Efforts to Increase the Effectiveness of Teacher Performance in the Learning Process Through Academic Supervision with a Collaborative Approach - Runtifasih, Runtifasih (PT FORMOSA CENDEKIA GLOBAL, 2023)
The aim of this research is to get an empirical picture of how teachers improve their performance in learning through academic supervision with a collaborative approach for teachers at SD Negeri Temanggal, Adimulyo District, Kebumen Regency in semester 2 of the 2022/2023 school year. This research uses School Action Research or School Action Research to see how teachers carry out learning in semester 2 of the 2022/2023 academic year at SD Negeri Temanggal, Adimulyo District, Kebumen Regency. Using Miles and Humberman's interactive model, data analysis was carried out in four stages: (1) data collection and review; (2) comparative description; (3) data presentation; and (4) draw verification of conclusions. Important findings in this research are: 1). Teacher performance continues to improve after academic supervision is carried out. 2). Academic supervision with a collaborative approach can increase learning effectiveness for teachers at SD Negeri Temanggal, Adimulyo District, Kebumen Regency.